2023
DOI: 10.1039/d3qo00415e
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Au(i)-catalyzed tandem reactions between 2-alkynyl enones and naphthols by the tethered counterion-directed catalysis strategy

Abstract: The enantioselective tandem cycloisomerization / addition reactions of 2-alkynyl enones with 1- and 2-naphthols have been investigated using gold(I) catalysts featuring hybrid phosphine-phosphoric acid chiral ligands, according to the Tethered...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…In further studies, we have demonstrated that naphthols can also be used as nucleophiles in the same tandem reactions [7d] …”
Section: Methodsmentioning
confidence: 91%
See 2 more Smart Citations
“…In further studies, we have demonstrated that naphthols can also be used as nucleophiles in the same tandem reactions [7d] …”
Section: Methodsmentioning
confidence: 91%
“…Our own studies [7d] established that, under CPAPhosAuCl catalysis, 2‐naphthols can behave as O ‐and/or C ‐nucleophiles [10] in their reaction with 1 , and that high enantioselectivities can be reached for both products 4 and 5 (Scheme 2, eq. 2), nicely complementing Ren's findings [9] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, Frison, Marinetti and Guinchard reported the gold( i )-catalysed enantioselective cycloisomerization/nucleophilic addition reaction of 2-alkynylenones ( 13a ) with naphthols ( 13k ) to produce bicyclic furans ( 13l and 13m ) (Scheme 13D). 113 The gold complexes of both ligands ( L13A and L13B ) can facilitate the desired reactions at low catalytic loading (0.2 to 1 mol%) and with significant enantioselectivities. Naphthol acts as an O-centered and C-centered nucleophile, leading to the highly enantioenriched bicyclic furans 13l (up to 85% ee) and 13m (up to 99% ee) respectively.…”
Section: Ligand Design For Asymmetric Gold(i) Catalysismentioning
confidence: 99%